Escalating the resolution of an urban aerial image via novel shadow amputation algorithm - Rani, E. Francy Irudaya; Pushparaj, T. Lurthu; Raj, E. Fantin Irudaya (Earth science informatics, 2022)
In order to produce better images, darkness identification and detection are essential in remote sensing techniques. Throughout this method, shadow attributes are carefully considered during contrast enhancement, and suspicious darkness is always derived based on the aforementioned image features. Furthermore, a few dark artifacts that could still be misinterpreted as shadows are rejected. The whole feature engineering is completely dependent upon the size of the object as well as their relative positions. The precedent set of the inside and outside highlight profile line (IOHPL) can be used to consider removing reflective surfaces from object categories. IOHPL segmental synchronization results in modules that are relatively homogeneous. Following that, the relatively homogenous sections are used to find the percentage light diagnostic specifications between both the shadow as well as non-shadow regions. This process will result in the effective removal of excess shadows or darkness in satellite-derived aerial urban images.